“Landscape is luxury”: Searching for Images of Sustainability - Cassatella, Claudia (AESOP, 2010)
Landscape can give an expressive form to ecological processes, give a vision for “green” policies and plans, and allow the public at large to understand what is at stake. Because most territorial changes are planned on the basis of various forms of representations and rendering, the power of images has grown more and more. What images of change are planners and designers putting forward? Are these images able to represent innovative scenarios of sustainability? The paper presents some case studies. The landscape is close to the way in which people perceive their own living environment, so it can be a powerful visioning tool for participatory democracy. It is proposed that the landscape debate should be reoriented, from the prevailing attention paid to the identity, as an heritage of the past, to a stronger focus on the “aspirations of the public” (European Landscape Convention) and to the creation of new landscape identities.
Book of proceedings: Annual AESOP Congress, 2010 Space is Luxury, Aalto, July 7-10th
Keywords: landscape theory; visioning; sustaining beauty